A Study on Effects of Chemical Fertilizer and Organic Manures on Kiwifruit (Actinidia deliciosa, cv. Hayward) Quality during Cold Storage - M. Kiaeshkevarian; T. Raiesi; B. Moradi; J. Fattahi Moghadam; M. Faghih Nasiri (Majallah-i ̒Ulum-i Bāghbānī, 2023)
Introduction Consumers demand for organic products is increasing due to their awareness of health and nutritional quality. Organic manures maintain soil health and ecological balance of the region. Organic agriculture, as an alternative agricultural system to protect human health and the environment can improve the quality and storability of the product. Kiwifruit is one of the most important agricultural products in north of Iran, which plays an effective role in trade and employment of the people. Fertilization is one of the main factors affecting the yield and quality of kiwifruit. Growers use organic manures and chemical fertilizers in their orchard to achieve higher yields. It is necessary to study the effect of various organic manures available in the region on the nutrition of kiwifruit vines due to increase chemical fertilizer prices and the formation of the market for organic fruits. Therefore, the aim of this study was to compare the effect of using five types of organic manures and chemical fertilizer on the quality of Hayward kiwi fruit during cold storage.